2012
DOI: 10.1186/1471-2458-12-661
|View full text |Cite
|
Sign up to set email alerts
|

Validation of sick leave measures: self-reported sick leave and sickness benefit data from a Danish national register compared to multiple workplace-registered sick leave spells in a Danish municipality

Abstract: BackgroundPrevious validation studies of sick leave measures have focused on self-reports. Register-based sick leave data are considered to be valid; however methodological problems may be associated with such data. A Danish national register on sickness benefit (DREAM) has been widely used in sick leave research. On the basis of sick leave records from 3,554 and 2,311 eldercare workers in 14 different workplaces, the aim of this study was to: 1) validate registered sickness benefit data from DREAM against wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 40 publications
0
112
0
Order By: Relevance
“…Further, information on sick leave was collected by self-report. However, the sensitivity and specificity of self-reports compared with registry-based sickness absence are acceptable for periods of sick leave not exceeding seven days [22]. In the present study, the majority of parents of survivors (70%) and bereaved parents (57%) reported sick leave of duration less than one week at T7.…”
Section: Strengths and Limitationsmentioning
confidence: 56%
“…Further, information on sick leave was collected by self-report. However, the sensitivity and specificity of self-reports compared with registry-based sickness absence are acceptable for periods of sick leave not exceeding seven days [22]. In the present study, the majority of parents of survivors (70%) and bereaved parents (57%) reported sick leave of duration less than one week at T7.…”
Section: Strengths and Limitationsmentioning
confidence: 56%
“…The sensitivity and the specificity were very high for ordinary sick leave, but very low for pregnancyrelated sick leave (26). We believe that this could be due to the exclusion of pregnancy-related sick leave or maternity leave (DREAM code 881) from the analyses.…”
Section: Hansen Et Almentioning
confidence: 92%
“…recently validated in a study comparing employer registration of sickness absence with DREAM registration (26). The sensitivity and the specificity were very high for ordinary sick leave, but very low for pregnancyrelated sick leave (26).…”
Section: Hansen Et Almentioning
confidence: 99%
“…Two studies were discarded because of incommensurate comparisons, since they matched selfreported and recorded absenteeism referring to different reasons (health problems versus general causes, Short et al, 2009) or to different absence indexes (time lost versus frequency of absence, Beehr & Gupta, 1978). In considering multiple statistics from the same study, we used the following criteria: when a study reported effect sizes or correlations separately for men and women, we averaged them between the two groups (Ferrie et al, 2005;Stapelfeldt, Jensen, Andersen, Fleten, & Nielsen, 2012;Voss, Stark, Alfredsson, Vingård, & Josephson, 2008); when a study reported statistics for multiple absence time periods we retained the 12 month data or that which best approximated that figure, since 12 months was the most common time frame among the studies (Grøvle et al, 2012;Revicki, Irwin, Reblando, & Simon, 2004;Severens, Mulder, Laheij, & Verbeek, 2000); where independent samples were investigated (Kessler et al, 2003), we coded these separately. This screening process resulted in a final set of 30 studies (27 published articles, 2 unpublished master's theses, 1 unpublished conference paper), containing 19 zero-order correlations for the convergent validity meta-analysis of correlations and 21 effect sizes for the accuracy meta-analysis using d. All zero-order correlations and effect sizes were based on independent samples except for the inclusion of Gaziel (2004), which reported both voluntary and involuntary absenteeism.…”
Section: Methods the Meta-analytic Databasesmentioning
confidence: 99%